2015
DOI: 10.1159/000438863
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected Ganglioneuroma of the Choroid Diagnosed after Enucleation

Abstract: We report a case of an unsuspected ganglioneuroma of the choroid in a patient with neurofibromatosis type 1. A 5-year-old girl presented from an outside institution with right proptosis and glaucoma since birth. Magnetic resonance imaging was obtained and showed a cavernous sinus mass extending into the right orbit and multiple orbital lesions. Additionally, increased signal in the posterior globe of the right eye was noted, but its etiology was unclear at the time. She was lost to follow-up for 3 years and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…These tumors can present with buphthalmos, intractable glaucoma, or as a blind, painful eye [1,2,3,4,5,6,7,8,9,10]. On review of the literature, we found only 9 prior cases of uveal ganglioneuroma reported [1,2,3,4,5,6,7,8,9,10], 7 of which were in the setting of newly diagnosed or previously established NF1 [1,2,3,4,5,6,7,8]. One case of choroidal ganglioneuroma without confirmed NF1 has been reported in the German literature [9], and 1 case was reported in the French literature of which details were not accessible [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tumors can present with buphthalmos, intractable glaucoma, or as a blind, painful eye [1,2,3,4,5,6,7,8,9,10]. On review of the literature, we found only 9 prior cases of uveal ganglioneuroma reported [1,2,3,4,5,6,7,8,9,10], 7 of which were in the setting of newly diagnosed or previously established NF1 [1,2,3,4,5,6,7,8]. One case of choroidal ganglioneuroma without confirmed NF1 has been reported in the German literature [9], and 1 case was reported in the French literature of which details were not accessible [10].…”
Section: Discussionmentioning
confidence: 99%
“…Ganglioneuroma of the choroid is a rare tumor usually associated with neurofibromatosis type 1 (NF1), with only 9 cases previously reported [1,2,3,4,5,6,7,8,9,10]. Cowden syndrome is caused by a germline mutation in the PTEN tumor suppressor gene and is characterized by hamartomatous growths as well as an increased risk for breast, thyroid, endometrial, renal, and gastrointestinal cancer [11].…”
Section: Introductionmentioning
confidence: 99%
“…They may be associated with multiple endocrine neoplasia type IIB and NF1. Since the first reported case of a choroidal neurofibroma containing ganglion cells in 1925, only a handful of cases have been discussed in the literature . Exceptionally, ganglion cells are also found in the ciliary body .…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature disclosed only 10 previous cases of uveal ganglioneuroma reported in the English literature. All of them were associated with NF1 (Table ) . The small number of cases reported to date precludes any valid assessment in terms of sex and age distribution of these uveal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal ganglioneuroma is an extremely rare disease, that only 13 cases have been reported in literatures [1][2][3][4][5][6][7][8][9][10][11][12][13] . Ganglioneuroma is benign neurogenic tumor that occurs with an approximate incidence of 1 case per million in the United States for children 14,15 .…”
Section: Introductionmentioning
confidence: 99%